Metformin immediate and extended-release adverse events and effects on metabolic parameters: a meta-analysis - Alshadfan, Hisham; Alamri, Marai; Mirghani, Hyder; Aljohani, Samar; Alanazi, Mansuor; Altemani, Faisal; Alqahtani, Majed; Albalawi, Ahmad; Humadi, Abdulaziz; Abdullah, Muhammad Nazrul Hakim (UbiJournal, 2023)
Metformin is the first-line antidiabetic medication, and face-to-face comparisons between immediate-release and extended-release are scarce. The current meta-analysis aimed to compare metformin's immediate and extended-release effects on glycemic control, adverse events, and lipid profile. We searched PubMed, Cochrane Library, and the first 100 articles in Google Scholar from inception until September 2022. Studies were eligible if they were randomized controlled trials and compared metformin's immediate and extended-release effects on glycemic control, adverse events, and lipid profile. The keywords used were metformin immediate-release, extended-release, glycated hemoglobin, HbA1c, high-density lipoproteins, low-density lipoproteins triglycerides, total cholesterol, adverse effects, and side effects. The retrieved data were exported to an Excel sheet detailing the authors' names, the country of origin of the study, the number of patients and control subjects, and the total number of events in the interventional and control groups. No significant statistical difference was found between metformin immediate-release and metformin extended-release regarding the reduction of HbA1c, overall adverse effects, low-density lipoproteins, and high-density lipoproteins; odd ratio, 0.08, 95 CI, -0.14-0.29; 1.34, 95 CI, 0.86-2.08; -0.03, 95 CI, -0.22-0.17; and -0.26, 95 CI, -1.32-0.80 respectively. Metformin immediate-released reduced total cholesterol better than the extended-release; odd ratio, -2.35, 95 CI, -2.57-2.12. However, a paradox was observed regarding triglycerides (increment on extended-release and reduction with extended-release); odd ratio, -0.36, 95 CI, -0.44-0.28. No significant differences were found between the two formulations except for a better triglyceride reduction and total cholesterol in the immediate-release arm.